Metastatic Malignant Ectomesenchymoma Initially Presenting as a Pelvic Mass: Report of a Case and Review of Literature - A. Nael; P. Siaghani; W. W. Wu; K. Nael; Lisa Shane; S. G. Romansky (Case Reports in Pediatrics)
Pediatric soft tissue sarcomas account for approximately 10% of all pediatric malignancies. Malignant ectomesenchymoma is rare biphasic sarcomas consisting of both mesenchymal and neuroectodermal elements. Approximately 64 cases have been reported in the literature and are believed to arise from pluripotent embryologic migratory neural crest cells. We report a 4-year-old boy who initially presented with a pelvic mass and inguinal lymphadenopathy at 6 months of age. Inguinal lymph node biopsy revealed a distinct biphasic tumor with microscopic and immunophenotypic characteristics diagnostic for both alveolar rhabdomyosarcoma and poorly differentiated neuroblastoma. The patient received national protocol chemotherapy against rhabdomyosarcoma with good response and presented with a cerebellar mass 21 months later. The metastatic tumor revealed sheets of primitive tumor cells and diagnostic areas of rhabdomyosarcoma and neuroblastoma were identified only by immunohistochemistry. Cytogenetic analysis of metastatic tumor demonstrated complex karyotype with multiple chromosomal deletions and duplications. The patient received national protocol chemotherapy against neuroblastoma and adjuvant radiotherapy after surgical resection of the cerebellar tumor with good response. He is currently off from any treatment for 18 months with no evidence of tumor recurrence or metastasis.